Epidermiological Approch to Predator-Prey Interaction - Mustapha, Faridah; Grinfeld, Michael (MATEMATIKA, 2002)
An epidemiological approch is used to model predator-prey interaction. The concept is borrowed from SIS model of disease transmission. In the predator-prey interaction, predation is viewed as a "disease" of the predator transmitted by the prey. In this approch, the predator population is partitioned into hungry and satisfied subpopulation. The stability of the steady states from the equations is analyzed. Keywords: Predator-prey interaction; Model SIS Pendekatan penyakit berjangkit digunakan untuk memodelkan intearksi mangsa-pemangsa. Konsep ini dipinjam daripada Model SIS jangkitan penyakit. Dalam interaksi mangsa-pemangsa, pemangsa dianggap sebagai "penyakit" pemangsa yang dijangkiti daripada mangsa. Pendekatan ini membahagikan populasi pemangsa kepada subpopulasi lapar dan kenyang. Kestabilan titik-titik kesimbangan daripada persamaan dianalisa. Katakunci: Intearksi mangsa-pemangsa; Model SIS